Chemoprotective effects of kolaviron on ethylene glycol monoethyl ether-induced pituitary-thyroid axis toxicity in male rats (2012)
Endocrine disrupting chemicals cause reproductive dysfunction by interacting with intricate regulation and cellular processes involve in spermatogenesis. This study investigated the probable mechanism of action of ethylene glycol monoethyl ether (EGEE) as an antiandrogenic compound as well as the effects of kolaviron upon co-administration with EGEE in rats. Adult male rats were exposed to EGEE (200 mg kg_1 bw) separately or in combination with either kolaviron [100 (KV1) and 200 (KV2) mg kg_1 bw] or vitamin E (50 mg kg_1bw) for 14 days. Western blot analysis revealed that the administration of EGEE adversely affected steroidogenesis in experimental rats by decreasing the expression of steroid acute regulatory (StAR) protein and androgen-binding protein (ABP). EGEE significantly decreased the activities of 3b-hydroxysteroid dehydrogenase (3b-HSD) and 17b-hydroxysteroid dehydrogenase (17b-HSD) but markedly increased sialic acid concentration in rat testes. EGEE-treated rats showed significant decreases in plasma levels of luteinising hormone (31%), testosterone (57.1%), prolactin (80.9%), triiodothyronine (65.3%) and thyroxine (41.4%), whereas follicle-stimulating hormone was significantly elevated by 76.9% compared to the control. However, co-administration of kolaviron or vitamin E significantly reversed the EGEE-induced steroidogenic dysfunction in rats. This study suggests that kolaviron may prove promising as a chemoprotective agent against endocrine pathology resulting from EGEE exposure.